Апроксимація екологічного законодавства України до права ЄС: аналіз міжнародної та національної правової бази - Сидор, В.; Sydor, V. (Східноєвропейський національний університет імені Лесі Українки, 2019)
В публікації проведено комплексний аналіз актів, що становлять правову основу процесу апроксимації екологічного законодавства України до права ЄС. Встановлено, що поступове приведення національного законодавства у відповідність із законодавством ЄС у галузі охорони навколишнього середовища та природокористування є однією з 16 пріоритетних сфер апроксимації. Досліджено юридичну природу основних етапів апроксимація екологічного законодавства: транспозицію, імплементацію та забезпечення впровадження. The legal basis and requirements for the process of approximation of the Ukrainian legislation to EU law in the environmental sector are defined as both the international legal norms of bilateral cooperation between Ukraine and the EU and the norms of the national legislation of Ukraine. The development and strengthening of cooperation on environmental issues will contribute to the long-term goals of sustainable development of the green economy. The cooperation in the field of environment protection must be carried out considering the interests of all countries in terms of equality and mutual benefit. Promising areas of cooperation can be the exchange of information and experience on environmentally clean technologies, joint research activities, joint disaster management and other emergencies, especially those of transboundary nature. The approximation process involves the adaptation of Ukraine's legislation, norms and standards to a similar EU legal framework in the field of the environment and implementation of the European standards for environmental protection and nature management. The gradual approximation of Ukraine's legislation to the EU law and policy in the field of environment protection is to be carried out through the implementation of the provisions of the EU laws and regulations in the following directions: environmental management and integration of environmental policy into other sectoral policies; air quality; waste management and resources; water quality and water management, including the marine environment; conservation; industrial pollution and man-made hazards; climate change and ozone layer protection; genetically modified organisms.
Approximation of the Environmental Legislation of Ukraine to the EU Law: Analysis of the International and National Legal Framework
Keywords: екологічне законодавства; навколишнє середовище; апроксимація; транспозиція; імплементація; впровадження; ecological legislation; environment; approximation; transposition; implementation